2009
DOI: 10.1007/s10397-009-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of TachoSil® to prevent postsurgical adhesion development on laparoscopic rat model

Abstract: The aim of this study was to evaluate the effectiveness of a fibrinogen and thrombin-coated hemostatic sponge (TachoSil®) in the prevention of postsurgical adhesions in a laparoscopic rat model and its histological effects on uterine and peritoneal parenchyma. Design was a prospective randomized blinded study. Setting was in International Laparoscopic Surgery Centre, ClermontFerrand, France. There were 100 sexually mature female Sprague-Dawley rats weighing 240 to 300 g and aged 6-8 weeks. A standardized sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…An important result of the present study is the fact that the Tachosil ® group showed fewer adhesions than the control group. Similar results were reported by two experimental studies where Tachosil ® reduced postoperative adhesions following laparoscopic surgery on a rat model and did not provoke adhesion formation in a pig model (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…An important result of the present study is the fact that the Tachosil ® group showed fewer adhesions than the control group. Similar results were reported by two experimental studies where Tachosil ® reduced postoperative adhesions following laparoscopic surgery on a rat model and did not provoke adhesion formation in a pig model (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…Other potential indications for the use of TachoSil include the reduction of postoperative adhesions after laparoscopic surgery and the prevention of heat-induced injuries to the uterine parenchyma (decline in fibrosis and inflammation), as indicated by findings in a rat model [15]. TachoComb was also capable of reducing adhesion reformation in a rabbit model [16].…”
Section: Discussionmentioning
confidence: 99%
“…Hemopatch™ (Baxter AG, Austria) is made from bovine collagen with reactive pentaerythritol polyethylene glycol ether tetra-succinimidyl glutarate (NHS-PEG) on the active side, which initiates the organisms own clotting mechanisms [8,9]. Veriset™ (Covidien, USA) is a cellulose matrix with a nonspecifi ed polyethylene glycol (PEG) on the active side [10,11].…”
Section: Introductionmentioning
confidence: 99%